2015
DOI: 10.2458/azu_rc.57.18350
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Radiocarbon Content in Plant Leaves in a 14C-Depleted Area

Abstract: The determination of radiocarbon content in biogenic samples such as tree leaves and short-lived plants is crucial when studying the anthropogenic impact on the ecosystem and for detecting any alteration in stable and radioactive CO 2 . A total of 76 samples of evergreen and deciduous tree leaves as well seasonal plants were collected in winter, spring, and summer. Sampling was carried out from rural villages located in Mount Lebanon Province, Lebanon. Based on the data obtained from a previous study carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Evergreen leaves may contain carbon fixed from the previous season or even previous years. The significant scatter of 14 C concentration (up to 70‰) in the plants growing polluted area comparing to the 14 C concentration in the plants growing in the clean area has been observed also by Baydoun et al (2015). Also the results of the systematic Δ 14 C measurements of soil CO 2 flux performed in the forest environment for 1998–2001, Gorczyca et al (2013) from closed-system gas collection at the soil surface suggested that Δ 14 C values of the CO 2 emitted from the forest soil were ~40‰ higher than current atmospheric background values.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Evergreen leaves may contain carbon fixed from the previous season or even previous years. The significant scatter of 14 C concentration (up to 70‰) in the plants growing polluted area comparing to the 14 C concentration in the plants growing in the clean area has been observed also by Baydoun et al (2015). Also the results of the systematic Δ 14 C measurements of soil CO 2 flux performed in the forest environment for 1998–2001, Gorczyca et al (2013) from closed-system gas collection at the soil surface suggested that Δ 14 C values of the CO 2 emitted from the forest soil were ~40‰ higher than current atmospheric background values.…”
Section: Resultssupporting
confidence: 68%
“…In terms of 14 C, the global CO 2 becomes depleted in 14 C, because the CO 2 from fossil fuels is devoid of any 14 C (Suess 1955). Local depletion of the radioactivity concentration (local Suess effect) can be observed in areas with higher CO 2 emissions from fossil fuel combustion (Rakowski et al 2000; Molnar et al 2007; Pazdur et al 2007; Svetlik et al 2010; Baydoun et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, our present results fully support that the evergreen leaves may contain 14 C fixed from previous years, as observed previously [ 20 , 22 ]. As a result, care should be taken when 14 C in the leaf of an evergreen tree is considered as a proxy for atmospheric 14 C with an annual time resolution.…”
Section: C Activitiessupporting
confidence: 92%
“…Increasing anthropogenic carbon dioxide emissions into the atmosphere due to the combustion of large amounts of fossil fuel combustion has changed the local and global carbon cycle. The impact of these carbon dioxide emissions on the isotopic concertation in trees (tree rings and foliage) is evident (Suess 1955;Molnar et al 2007;Hua et al 2013;Pazdur et al 2013;Baydoun et al 2015;Ndeye et al 2017). The physiological processes of trees, such as their photosynthesis rate and stomatal conductance, can be affected not only by carbon dioxide, but also by other air contaminants, gases, and dust associated with human activities, such as industrial processes, road transport, and low and high-stack emissions (Staszewski et al 1994).…”
Section: Introductionmentioning
confidence: 99%